Analysis of Land Suitability for Superior Commodities in Nagari Lawang, Matur District, Agam Regency: Analisis Kesesuaian Lahan untuk Komoditas Unggulan di Nagari Lawang, Kecamatan Matur, Kabupaten Agam - Nurdiyanto, Muhammad Rizki Dhani; Yanti, Delvi; Irsyad, Fadli; Stiyanto, Eri (Universitas Brawijaya, 2025)
This research has been carried out to identify areas that were suitable for planting superior crops in Nagari Lawang, Matur District, Agam Regency. This research was conducted using the matching method and then was continued with scoring of the slope, rainfall, C-Organic, soil pH, and soil texture parameters. The obtained values ??were used to determine the classification of land suitability for sugar cane, corn, peanuts and shallots. Land with the potential for planting sugar cane, corn, peanuts, and shallots is land in the very suitable (S1) and suitable (S2) suitability classes. Several commodities can be planted on a piece of land depending on the suitability of the characteristics of the land to the conditions for growing plants. The results of the analysis show that the land in Nagari Lawang that is suitable for planting sugar cane is 380.23 ha (27.57%), corn is 380.23 ha (27.57%), peanuts is 362.57 ha (26.29%), and shallots is 380.23 ha (27.57%) of the total land area of ??Nagari Lawang. Nagari Lawang's land (2023) that has been planted (S1 and S2 classes) with sugar cane covers an area of ??184.26 ha, corn covers an area of ??2.6 ha, peanuts covers an area of ??2.09 ha, and shallots covers an area of ??0.12 ha. The potential for developing sugar cane is 195.97 ha, corn is 377.63 ha, peanuts is 360.48 ha and shallots is 380.11 ha, respectively.